Der Krustenaufbau des Norwegischen Kontinentalrandes (Voring Plateau) und der Norwegischen Tiefsee zwischen 66° und 68° N nach seismischen Untersuchungen - Hinz, K. (Bornträger, 1972)
Based on refraction seismic measurements a crustal profile starting from the Norwegian shelf, crossing the Voring Plateau, the Norwegian deep sea basin and ending at the foot of the Jan Mayen Ridge is constructed. The Voring Plateau is divided into a western continental fragment and an eastern Graben Zone under which the Upper Mantle is uplifted. The deep sea has a bloc-structure with basic intrusive bodies. The deep part of the Jan Mayen Ridge has an oceanic crust.